A case study: the impact of using digital technology on learning behavior among students at national archives of Malaysia, Kedah & Perlis branch / Ku Nurizzaty Ku Rosli - Ku Rosli, Ku Nurizzaty (2014)
With the advance of the technology, digital technology such as computer, smartphones, digital cameras and many others digital tools are no longer exclusive for certain group. Nowadays, digital technology has emerged as one of the teaming tool to assist in the learning process. As we know students all over the world use computers and Internet technology, thereby informally learning how to learn with the technology. It is widely argued that technology, computers and the Internet shape how we think. Thus, in this research, a few issue will be focused; the trend of using digital technology among students, the contributing factors which is internal and external factors why student choose digital technology in learning, and lastly what is the impact of using digital media on the student's learning behavior.